2021
DOI: 10.48550/arxiv.2109.02884
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Next-to-leading-order corrections to the Higgs strahlung process from electron-positron collisions in extended Higgs models

Masashi Aiko,
Shinya Kanemura,
Kentarou Mawatari

Abstract: We present the cross section for e + e − → hZ with arbitrary sets of electron and Z boson polarizations at the full next-to-leading order in various extended Higgs models, such as the Higgs singlet model (HSM), the inert doublet model (IDM) and the two Higgs doublet model (2HDM). We systematically perform complete one-loop calculations to the helicity amplitudes in the on-shell renormalization scheme, and present the full analytic results as well as numerical evaluations. The deviation ∆R hZ in the total cross… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 83 publications
(117 reference statements)
0
3
0
Order By: Relevance
“…The rich phenomenology of the IDM has been thoroughly studied in the literature, both in the context of future Higgs factories like the ILC and CLIC and at the LHC . Additionally, there have been many studies of the model that go beyond the lowest order of the perturbation, including those at one-loop level [58][59][60][61][62][63][64][65][66][67][68][69][70][71][72][73] and two-loop order [74][75][76]. The one-loop contributions to the triple Higgs boson coupling from Standard Model particles have been investigated in [58,[77][78][79][80], where it was found that these corrections are dominated by loops involving the top quark.…”
Section: Introductionmentioning
confidence: 99%
“…The rich phenomenology of the IDM has been thoroughly studied in the literature, both in the context of future Higgs factories like the ILC and CLIC and at the LHC . Additionally, there have been many studies of the model that go beyond the lowest order of the perturbation, including those at one-loop level [58][59][60][61][62][63][64][65][66][67][68][69][70][71][72][73] and two-loop order [74][75][76]. The one-loop contributions to the triple Higgs boson coupling from Standard Model particles have been investigated in [58,[77][78][79][80], where it was found that these corrections are dominated by loops involving the top quark.…”
Section: Introductionmentioning
confidence: 99%
“…In order to obtain a sufficient accuracy, one-loop corrections to the various charged Higgs boson production modes and its couplings have to be considered. Recently, one loop radiative corrections to e + e − → Zh 0 [82][83][84] and e + e − → H 0 A 0 [82] in the IHDM have been evaluated. In addition, there are many other works dealing with radiative corrections in the IHDM either at one loop order [82][83][84][85][86][87][88][89][90][91][92][93] or beyond the one-loop level [94][95][96].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, one loop radiative corrections to e + e − → Zh 0 [82][83][84] and e + e − → H 0 A 0 [82] in the IHDM have been evaluated. In addition, there are many other works dealing with radiative corrections in the IHDM either at one loop order [82][83][84][85][86][87][88][89][90][91][92][93] or beyond the one-loop level [94][95][96]. Full one-loop calculations to e + e − → H + H − in non-supersymmetric models such as the two Higgs doublet model (2HDM) and some supersymmetric models like the real MSSM (rMSSM) and complex MSSM (cMSSM) have been presented in Refs [97][98][99][100][101][102][103][104].…”
Section: Introductionmentioning
confidence: 99%